2018
DOI: 10.1007/s00432-018-2715-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there a benefit of lymphadenectomy for overall and recurrence-free survival in type I FIGO IB G1-2 endometrial carcinoma? A retrospective population-based cohort analysis

Abstract: In contrast to previous observations in high-grade EC, our study provides compelling evidence that LND, in particular systematic lymphadenectomy, is not beneficial for patients with type I FIGO IB EC in terms of long-term OAS and RFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Venigalla et al observed an improvement in overall survival after pelvic lymphadenectomy or with no pelvic lymphadenectomy in high-risk cancers [15]. Also, Papathemelis et al in the study in 2017 reported a significant effect of systematic pelvic and paraaortic lymphadenectomy in reduction of recurrence rate and longer overall survival, while in 2018 Papathemelis et al found lower effect of lymphadenectomy in patients with low grade endometrial cancer [16,17]. Konno et al reported studies with no lymphadenectomy in endometrial cancer, which could be preferred in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venigalla et al observed an improvement in overall survival after pelvic lymphadenectomy or with no pelvic lymphadenectomy in high-risk cancers [15]. Also, Papathemelis et al in the study in 2017 reported a significant effect of systematic pelvic and paraaortic lymphadenectomy in reduction of recurrence rate and longer overall survival, while in 2018 Papathemelis et al found lower effect of lymphadenectomy in patients with low grade endometrial cancer [16,17]. Konno et al reported studies with no lymphadenectomy in endometrial cancer, which could be preferred in practice.…”
Section: Discussionmentioning
confidence: 99%
“…In this group, only one patient had undergone laparotomy in the past. The mean number of paraaortic lymph nodes was 15.87 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and the mean number of pelvic lymph nodes was 24.5 (14-43). The mean operative time was 177 (110-235) min.…”
Section: Docking and Lymphadenectomymentioning
confidence: 99%
“…The benefit of lymphadenectomy in EC patients has been a controversial topic for over a decade (12)(13)(14). The survival advantage associated with lymphadenectomy exists primarily in patients with a relatively high risk of recurrence (14)(15)(16)(17)(18), and improperly expanding the indication of lymphadenectomy might result in more adverse effects instead (19)(20)(21)(22)(23)(24)(25). Our research didn't support the role of lymphadenectomy in preventing LNR in terms of the scope and number of LNs harvest, with agreement with Mariani et al (5).…”
Section: Discussionmentioning
confidence: 99%
“…The patient age, which has been incorporated into the existing risk classification systems [ 5 , 6 ], may influence the effect of lymphadenectomy in endometrioid endometrial carcinoma ( Table 3 ). In elderly women, lymphadenectomy may be less effective than in younger women, which might be indicated in German population-based studies where median age of the patients was 69 years or older [ 127 , 128 ]. This may be explained by the association of older age with adverse pathologic features [ 129 , 130 ], hematogenous dissemination [ 118 ], and immunosenescence [ 131 ].…”
Section: Benefit Of Systematic Lymphadenectomy In Node-negative Patie...mentioning
confidence: 99%